The Critical Intersection Point of a Nation: Reading the Traces of the Concept of the Nation in the Indonesian Novel - Akhmad Taufiq; Nanda Saputra (LingLit Journal Scientific Journal for Linguistics and Literature, 2022)
The phenomenon of the nation, along with its concept, is not stable. It develops constantly and is dynamic. This study aims to describe the traces of the dynamics of the concept of the nation in the Indonesian novel. With an interpretive qualitative descriptive method, which supports data in the form of Indonesian novel texts; namely the novel Salah Asuhan by Abdoel Moeis and Tanah Air Beta by Sefryana Khairil, this study seeks to explain the occurrence of events of change or shifting concepts with regard to the nation. Based on this, the results of this study show that in the text of Indonesian novels, especially the two novels, it was found that the concept of the nation was not stable. The concept of the nation can move, shift, and allow separation, which can result in the occurrence of a critical intersection point of a nation. On this basis, the implication of this study is the importance of continuously observing the dynamics of the concept of the nation. Along with that, it is necessary to maintain continuously the commitment of the nation that has been formed.